Comparison of the effects of different types of treatment protocols on the median and overall survival rates of non-small cell lung cancer patients: A real-world retrospective study - Tarza Jamal Siahmansur (PLoS ONE, 2026)
Lung cancer treatment presents a major challenge globally. The advent of monoclonal antibodies (mAbs) has ushered in a new era in the treatment of non-small cell lung cancer (NSCLC). This study aimed to investigate the impact of the addition of mAbs to platinum-based doublet therapy on overall survival in NSCLC patients and the difference in median survival among patients treated with different treatment protocols. In this study, demographic, clinical, and therapeutic data from 359 NSCLC patients were recorded, and the histopathological and disease stages of the patients, along with the site of metastasis, were documented. The median survival rates, 1-, 3-, and 5-year survival rates, covariate hazard ratios, and independent predictors of overall survival were analyzed. Statistically significant differences were observed in the median survival of patients treated with different treatment protocols ( p = 0.002). Comparing therapies, patients treated with carboplatin/paclitaxel+anti-PD-1/anti-PD-L1 mAb or cisplatin/vinorelbine+anti-PD-1/anti-PD-L1 mAb had highest median survival (median survival months ± SE) (49.4 months ± 9.15 and 34.9 months ± 8.61 respectively) with lowest hazard ratio (HR = 0.032; 95% confidence interval (CI) [0.003–0.310], p = 0.003 and HR = 0.048; 95% CI [0.005–0.465], p = 0.0083 respectively). Patients treated with triple therapy [platinum-based doublet chemotherapy combined with mAb drugs had significantly ( p = 0.01) greater median survival (20.7 months ± 3.11; HR = 0.593; 95% CI [0.443–0.794], p = 0.00046) compared to patients treated with platinum-based doublet chemotherapy with concurrent radiation (13.6 months ± 3.8; HR = 0.742 95% CI, [0.531–1.035], p = 0.07884] or patients treated with platinum-based doublet chemotherapy (9.1 months ± 0.68; HR = 1) or single treatment (12.9 months ±3.81; HR = 0.927; 95% CI [0.629–1.365], p = 0.69970) and better 1-, 3-, and 5-year survival rates (95% CI) [66.20% (0.554–0.77), 26.40% (0.162–0.366), and16.25% (0.065–0.261) respectively] than patients treated with platinum-based doublet chemotherapy with concurrent radiation [54% (0.403–0.677), 22% (0.104–0.336), and 4% (0.001–0.079) respectively] or without concurrent radiation [39.10% (0.324–0.458), 12.80% (0.081–0.175) and 3.57% (0.012–0.381) respectively] or single treatment [51.50% (0.407–0.623), 12.12% (0.0193–0.223), and 10.12% (0.003–0.199) respectively]. The statistically significant predictors for overall survival were cancer metastasis ( p = 0.0001), disease stage at diagnosis ( p = 0.001), patient age ( p = 0.017), and performance of lung resection surgery ( p = 0.021). 64.1% of the patients had metastasis, and they had significantly lower median survival than patients without metastasis ( p = 0.0001). Multi-organ metastasis was the most common type of metastasis (20.9%). In conclusion, the addition of mAbs such as anti-programmed cell death protein 1/programmed death-ligand 1 or epidermal growth factor receptor inhibitors or vascular endothelial growth factor inhibitors to platinum-doublet chemotherapy markedly improved the overall survival and survival rates of NSCLC patients.